Green Finance and Its Role in Promoting Sustainable Investment in Emerging Markets - Subagiya Subagiya; Miranda Dhyta; Amri Amri; Seno Hadi (Jurnal Multidisiplin Sahombu, 2026)
This study comprehensively examines the role of green finance as a catalyst for sustainable investment in emerging markets, focusing specifically on Indonesia. Employing a quantitative research design integrating panel data regression, propensity score matching, and event study methodologies, this research analyzes the relationship between green finance instruments including green bonds, green loans, and ESG integration and sustainable investment outcomes. The empirical findings demonstrate that access to green finance significantly increases sustainable investment volumes by approximately 15 20%, while ESG integration positively affects corporate financial performance with a one standard deviation increase in ESG scores associated with 0.8 1.2 percentage points ROA improvement. Results validate five key hypotheses linking green finance availability, ESG integration, policy frameworks, sustainable banking practices, and institutional investor behavior to sustainable investment outcomes. The study reveals that policy support through Indonesia's Sustainable Finance Roadmap significantly enhances green bond issuance and lending volumes, while sustainable banking practices enable financial institutions to allocate 12 18% of loan portfolios to green lending. Market responses to green bond issuances present mixed results, indicating investors are still learning about green finance instrument valuation. The research provides substantial practical implications for policymakers, financial institutions, corporations, and investors, emphasizing the importance of comprehensive policy frameworks, ESG integration, and credible disclosure mechanisms in advancing sustainable finance in emerging market contexts.